Shape memory polymer microsphere as well as preparation method and application thereof
The preparation of shape memory epoxy polymer microspheres through Pickering emulsion polymerization solves the problems of difficulty and high consumption of existing materials, and realizes the method of directly preparing microspheres without crushing, which improves the application efficiency and economicality of the materials.
Patent Information
- Application Number
- CN202311236022.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-03-25
AI Technical Summary
The existing shape memory epoxy polymer materials are difficult and consumed during the crushing process, resulting in high economic costs and making it difficult to prepare particles and sheets of required particle sizes.
Millimeter and micron-scale shape memory epoxy polymer microspheres were prepared by polymerization of Pickering emulsion. Pickering emulsion was formed by mixing epoxy resin, curing agent, organic solvent and stabilizer, and pressing it after the reaction to obtain shape memory polymer microspheres.
Shape memory polymer microspheres can be prepared without crushing, which are directly used in oil and gas mining drilling, cementing temperature-sensitive cement materials or cement expansion agent materials, improving the application efficiency and economicality of the materials.
Smart Images

Figure CN119684641A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of smart materials, and more specifically, to a shape memory polymer microsphere and a preparation method and application thereof. Background Art
[0002] Shape memory materials are a type of smart material that can return to its original shape under external stimuli such as temperature, pressure, light, electricity, and magnetism. Among them, shape memory polymer materials are widely used in aerospace, construction, medicine, textiles and other fields because of their advantages such as easy processing, low density, large deformation, excellent mechanical properties, multiple stimulation methods, and adjustable activation temperature and time.
[0003] In the field of oil extraction, as oil and gas development gradually moves towards complex formations such as deep and high temperatures, shape memory polymer materials as intelligent plugging materials have shown obvious advantages over conventional plugging materials in terms of efficient pressure-bearing plugging, such as: small volume at room temperature, easy to transport to the leaking layer while drilling; with the help of temperature activation, expansion and stretching of the leaking layer, a dense pressure-bearing plugging layer can be quickly and efficiently constructed; adaptive bridging plugging is performed within a certain range without clarifying the opening of the formation fractures, which reduces the selectivity of the formation fractures for the size of the plugging material and improves the pressure-bearing plugging capacity and adaptability of the fractures. In addition, in terms of plugging with cement in oilfield cementing and improving the quality of cement cementing, shape memory polymer materials can be used to develop temperature-sensitive plugging cement slurry, and shape memory materials can be used as cement expansion agents and cement toughening modifiers to effectively improve the quality and efficiency of cementing.
[0004] When using shape memory polymer materials to prepare intelligent plugging, cement expansion agents and other materials, considering the application of high-temperature formations, the shape memory polymer materials need to have a higher excitation transition temperature. Epoxy polymer is a thermosetting polymer material, and its highly cross-linked structure gives it excellent thermal and mechanical properties. At present, researchers have developed shape memory epoxy polymer plugging materials based on the plugging characteristics of high-temperature formations. The excitation transition temperature is generally 70-110°C; when used as an intelligent plugging material, the epoxy polymer material needs to be pressed and formed above the excitation transition temperature, cooled and shaped, and then crushed into particles or fragments for use. The resulting epoxy polymer material usually has high strength and modulus. It is first made into large pieces or large pieces of macroscopic materials, and then crushed into particles or sheets. The crushing process is very difficult, and the consumption of particles and sheets of the required particle size is large, and the economic cost is high. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a shape memory polymer microsphere and a preparation method and application thereof. The present invention utilizes Pickering emulsion polymerization to prepare millimeter and micron-sized shape memory epoxy polymer microspheres, which do not need to be crushed and can be directly used as intelligent plugging materials for oil and gas drilling, cementing temperature-sensitive cement materials or cement expansion agent materials, etc.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing shape memory polymer microspheres, comprising:
[0008] (1) mixing an epoxy resin, a curing agent, an organic solvent and a stabilizer to form a Pickering emulsion;
[0009] (2) mixing the Pickering emulsion and the accelerator, reacting to obtain polymer microspheres, and pressing to obtain shape memory polymer microspheres;
[0010] The stabilizer includes nanoparticles and / or nanosheets.
[0011] In the present invention, the stabilizer includes one or more of graphene nanosheets, zinc oxide nanoparticles, titanium dioxide nanoparticles, and silicon dioxide nanoparticles, preferably silicon dioxide nanoparticles; the particle size of the nanoparticles is 20nm; the surface of the nanoparticles may contain amino groups and epoxy groups; the mass content of the stabilizer in the Pickering emulsion is 0.08% to 1.6%.
[0012] In the present invention, the organic solvent includes ethanol; the step (1) preferably includes: mixing the epoxy resin with the organic solvent to form an epoxy resin solution; mixing the curing agent with the organic solvent to form a curing agent solution; mixing the stabilizer with the epoxy resin solution and the curing agent solution respectively to form a Pickering emulsion; preferably, adding the epoxy resin solution and the curing agent solution to the stabilizer.
[0013] In the present invention, the stabilizer is preferably mixed with the epoxy resin, the curing agent and the organic solvent in the form of a solution. The stabilizer is preferably first dissolved in water or an organic solvent and then mixed with the epoxy resin, the curing agent and the organic solvent.
[0014] In the present invention, it is preferred to add an accelerator to the Pickering emulsion.
[0015] In the present invention, the preparation method of the shape memory polymer microspheres also includes: post-processing the obtained shape memory polymer microspheres; the post-processing includes impurity removal and drying; the impurity removal preferably includes: centrifugation first, then washing; the solvents used for washing are water and ethanol; the drying is carried out at 50-60°C.
[0016] In the present invention, the reaction temperature is 80-95° C. and the reaction time is 4-6 hours.
[0017] In the present invention, the reaction is carried out under stirring conditions; the stirring speed is 300-600 rpm.
[0018] In the present invention, the compression rate of the pressing is 20% to 50%; the pressing pressure is 1 to 10 MPa; the pressing temperature is the glass transition temperature of the polymer microspheres + 20° C., preferably 110 to 180° C. After pressing, the flattened shape memory polymer particles are obtained, and when the temperature is raised to the excitation transition temperature, i.e., the glass transition temperature Tg, the initial spherical particle morphology can be restored.
[0019] In the present invention, the epoxy resin includes one or more epoxy monomers; the epoxy monomers contain 2 to 4 epoxy groups; the epoxy resin includes one or more of bisphenol A diglycidyl ether, trimethylolpropane triglycidyl ether, N,N-diglycidyl-4-glycidyloxyaniline, and 4,4-diaminodiphenylmethane tetraglycidylamine;
[0020] The mass content of the epoxy resin in the Pickering emulsion is 9% to 24%.
[0021] In the present invention, the curing agent includes a polyamine curing agent; the curing agent includes one or more of vinylamine, polyetheramine, aromatic amine, and polyamine containing disulfide bonds; the vinylamine includes one or more of diethylenetriamine, triethylenetetramine, tetraethylenepentamine, and hydroxyethylethylenediamine; the aromatic amine includes one or more of diaminodiphenylmethane, 4,4-diaminodiphenyl sulfone, and 4,4'-diaminodiphenyl ether; the polyetheramine includes polyetheramine D230; the polyamine containing disulfide bonds includes 4,4' disulfide diphenylamine;
[0022] The mass content of the curing agent in the Pickering emulsion is 5% to 12%.
[0023] In the present invention, the stabilizer comprises a nonionic surfactant; the nonionic surfactant comprises polyvinyl pyrrolidone and / or polyvinyl alcohol; the mass content of the nonionic surfactant in the Pickering emulsion is 5% to 12%.
[0024] In the present invention, the accelerator includes a tertiary amine accelerator; the accelerator includes one or more of benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicycloundec-7-ene; the volume ratio of the Pickering emulsion to the accelerator is 1:(0.001-0.005), preferably 1:(0.001-0.002).
[0025] The present invention also provides shape memory polymer microspheres prepared by the preparation method of the shape memory polymer microspheres.
[0026] The shape memory polymer microspheres of the present invention have a D50 particle size of 5 μm-2.2 mm.
[0027] The present invention also provides the use of the shape memory polymer microspheres in the preparation of intelligent plugging materials for oil and gas drilling, well cementing temperature-sensitive cement materials or cement expansion agent materials.
[0028] In view of the difficulty in crushing the shape memory epoxy polymer materials used for drilling plugging, the present invention utilizes Pickering emulsion polymerization to prepare millimeter and micrometer-sized shape memory epoxy polymer microspheres, which do not need to be crushed and can be directly used as intelligent plugging materials for oil and gas drilling, temperature-sensitive cement materials for cementing or cement expansion agent materials, etc.
[0029] It has been confirmed by the embodiments of the present invention that the glass transition temperature Tg of the epoxy polymer microspheres obtained by differential scanning calorimetry (DSC) is 90-160°C, and the epoxy polymer microspheres obtained are pressed at a temperature of Tg+20°C, and the compression rate of the microspheres is 20%-50% when observed and calculated using a scanning electron microscope or an optical microscope; and when the temperature is then raised to the glass transition temperature Tg of the microspheres, the shape recovery rate is 95-99%. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is a SEM photograph of 5-7 μm epoxy polymer microspheres in Example 1 of the present invention;
[0031] Figure 2 This is a digital photo of 1.7-2 mm epoxy polymer microspheres in Example 5 of the present invention;
[0032] Figure 3 These are digital photos of 2 mm epoxy polymer microspheres after compression (A) and after returning to spherical shape (B) in Example 6 of the present invention. DETAILED DESCRIPTION
[0033] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] In order to further illustrate the present invention, the following examples are provided for detailed description. The raw materials used in the following examples of the present invention are all commercially available commodities.
[0035] The test method used in the embodiment of the present invention is as follows:
[0036] 1) Cement solidification compressive strength and toughness test
[0037] Use G-grade cement to prepare cement slurry with a water-cement ratio of 0.44, add the prepared shape memory polymer microspheres (4-6%, relative to the cement mass) to the cement slurry, pour into a mold, and cure at the Tg of the shape memory polymer microspheres (Example 1-4, Tg = 90-150° C.) for 7 days to obtain a 50×50×50 mm solidified body;
[0038] Comparative experiment: using cement paste without shape memory polymer microspheres to prepare the solidified body for testing;
[0039] The compressive strength of cement solidified bodies with and without shape memory polymer microspheres was measured using a uniform loading press according to the method in NB / T 14004.2-2016.
[0040] The stress-strain curve obtained from the compressive strength test was used to determine the strain (ε No ), the strain of the cement solidified body with shape memory polymer microspheres at the maximum compressive strength (ε P ), the toughness improvement rate (%) of the cement solidified body with the addition of shape memory polymer microspheres is calculated as follows:
[0041]
[0042] 2) Sealing performance
[0043] The long slit plugging test device is used to test the plugging performance:
[0044] Calcium carbonate particles (8%) and fibers (0.2%) were added to 4% bentonite-based slurry to form a basic experimental slurry;
[0045] Adding the prepared shape memory polymer microspheres (4-5%, mass percentage in the experimental slurry) to the above basic experimental slurry to form a sample experimental slurry;
[0046] A long slit plugging experimental device (the opening of the slits is 3×2mm and 2×1mm) was used to test the plugging performance of the basic experimental slurry and the sample experimental slurry under the Tg of the shape memory polymer microspheres (Example 5, Tg=160°C, Example 6, Tg=150°C); when tested at the Tg temperature, the basic experimental slurry completely leaked, the sample experimental slurry could withstand a pressure of 7.6-9.2MPa, and the leakage was less than 150ml.
[0047] Using sand bed to test plugging performance:
[0048] A sand bed was filled with 100-120 mesh quartz sand, and a basic experimental slurry was prepared using 4% bentonite slurry, 0.1% xanthan gum, and 5% calcium carbonate powder (200 mesh); 5% shape memory polymer microspheres (Example 7) were added to the basic experimental slurry to prepare a sample experimental slurry;
[0049] The plugging performance was tested at the Tg temperature of the shape memory polymer microspheres (Example 7, Tg = 123°C) using a sand bed leakage test device, and the penetration depth and pressure bearing capacity of the experimental slurry in the sand bed were determined.
[0050] Example 1
[0051] The method for preparing the shaped polymer microspheres of this embodiment comprises the following steps:
[0052] (1) dissolving epoxy monomer E51 (the mass percentage in Pickering emulsion is 24%) in part of ethanol (60% of the total ethanol volume), dissolving curing agent diaminodiphenylmethane (the mass percentage in Pickering emulsion is 5%, and the meanings expressed in the following examples are abbreviated as percentages) in part of ethanol (40% of the total ethanol volume); dissolving surfactant polyvinylpyrrolidone (PVP30K, the mass percentage in Pickering emulsion is 5%) in water, and the volume ratio of the total ethanol volume to the water volume is 8 / 2; then adding silicon dioxide nanoparticles (SiO2NPs, the mass percentage in Pickering emulsion is 0.8%), and ultrasonically dispersing to form an aqueous phase;
[0053] (2) Place the three-necked flask in a constant temperature water bath at 80°C, add the aqueous dispersion containing PVP30K and SiO2NPs, start stirring at a speed of 300 rpm, add the ethanol solution of epoxy monomer and the ethanol solution of curing agent, and stir to form a Pickering emulsion; add 100 μl of accelerator 1,8-diazabicycloundec-7-ene-DBU to 100 mL of Pickering emulsion to start the reaction; after reacting for 4 hours, the obtained epoxy polymer microspheres are precipitated, centrifuged, washed with water and ethanol three times, and dried in an oven at 50°C, and pressed at 140°C with a pressure of 5 MPa, with a compression rate of 20%, and then heated to 120°C, with a shape recovery rate of 95%, to obtain shape memory polymer microspheres;
[0054] (3) SEM observation showed that the particle size D50 of the obtained microspheres was 5-7 μm and the glass transition temperature Tg was 120°C.
[0055] The shape memory polymer microspheres of this embodiment are suitable for preparing cement slurry with G-grade cement and a water-cement ratio of 0.44. The compressed memory microspheres (5%, relative to the cement mass) are added to the slurry, poured into a mold, and cured at 120°C for 7 days. The compressive strength of the solidified body is measured by a uniform load press and is 23.7 MPa. Compared with the compressive strength of the cement slurry solidified body without the addition of memory microspheres, which is 16.3 MPa, the compressive strength of the cement slurry solidified body with the addition of memory microspheres is increased by 45%, and the toughness is increased by 21%.
[0056] Example 2
[0057] The preparation method of the shaped polymer microspheres of this embodiment refers to the steps in Example 1, except that: the epoxy monomers used in this embodiment are E51 (21%) and 4.4-diaminodiphenylmethane tetraglycidylamine - TGMDA (3%), the curing agent is triethylenetetramine TETA (10%) and polyetheramine D230 (2%), the surfactant used is polyvinylpyrrolidone PVP30K (12%), SiO2NPs (1.6%), the volume ratio of ethanol to water is 7 / 3, the reaction is carried out in a constant temperature water bath at 95°C, the speed is 600rpm, 200μl of accelerator 2,4,6-tris(dimethylaminomethyl)phenol-DMP-30 is added, and the reaction is carried out for 4h; the particle size D50 of the obtained microspheres is 8-10μm, the glass transition temperature Tg is 140°C, the compression rate is 25% at 160°C, and the shape recovery rate is 95% when the temperature is raised to 140°C.
[0058] The shape memory polymer microspheres of this embodiment are suitable for preparing cement slurry with G-grade cement and a water-cement ratio of 0.44. The compressed memory microspheres (6%, relative to the cement mass) are added, and the prepared slurry is poured into a mold and cured at 140°C for 7 days. The compressive strength of the solidified body is measured by a uniform loading press and is 25.8 MPa. Compared with the compressive strength of the cement slurry solidified body without the addition of memory microspheres, which is 16.3 MPa, the compressive strength of the cement slurry solidified body with the addition of memory microspheres is increased by 58%, and the toughness is increased by 19%.
[0059] Example 3
[0060] The preparation method of the shaped polymer microspheres of this embodiment refers to the steps in Example 1, except that: the epoxy monomers used are E44 (7%) and trimethylolpropane triglycidyl ether-TMTGE (2%), the curing agents used are tetraethylenepentamine TEPA (10%) and polyetheramine D230 (2%), the surfactant used is polyvinyl alcohol (PEG200, 10%), the SiO2NPs used are particles containing amino groups on the surface (SiO2-NH2NPs, 0.08%), the volume ratio of ethanol to water is 4 / 6, the reaction is carried out in a constant temperature water bath at 85°C, the rotation speed is 300rpm, 100μl of accelerator benzyldimethylamine-BDMA is added, and the reaction is carried out for 6h; the particle size D50 of the obtained microspheres is 400-430μm, the glass transition temperature Tg is 90°C, the compression rate is 50% at 110°C, and the shape recovery rate is 99% when the temperature is raised to 90°C.
[0061] The shape memory polymer microspheres of this embodiment are suitable for preparing cement slurry with G-grade cement and a water-cement ratio of 0.44. The compressed memory microspheres (4%, relative to the cement mass) are added, and the prepared slurry is poured into a mold and cured at 90°C for 7 days. The compressive strength of the solidified body is measured by a uniform loading press and is 19.7 MPa. Compared with the compressive strength of the cement slurry solidified body without the addition of memory microspheres, which is 16.3 MPa, the compressive strength of the cement slurry solidified body with the addition of memory microspheres is increased by 21%, and the toughness is increased by 31%.
[0062] Example 4
[0063] The preparation method of the shaped polymer microspheres of this embodiment refers to the steps in Example 1, except that: the epoxy monomers used are E51 (14%) and N,N-diglycidyl-4-glycidyloxyaniline TGPAP (3%), the curing agents used are 4,4'-diaminodiphenyl ether-OBA (6%) and polyetheramine D230 (3%), the surfactant used is PVP30K (8%), the SiO2NPs used are particles containing epoxy groups on the surface (SiO2-EP NPs, 0.8%), the volume ratio of ethanol to water is 3 / 7, the reaction is carried out in a constant temperature water bath at 85°C, the rotation speed is 300rpm, 100μl of accelerator DBU is added, and the reaction is carried out for 6h; the particle size D50 of the obtained microspheres is 500-520μm, the glass transition temperature Tg is 150°C, the compression rate is 30% at 170°C, and the shape recovery rate is 96% when the temperature is raised to 150°C.
[0064] The shape memory polymer microspheres of this embodiment are suitable for preparing cement slurry with G-grade cement and a water-cement ratio of 0.44. The compressed memory microspheres (5%, relative to the cement mass) are added, and the prepared slurry is poured into a mold and cured at 150°C for 7 days. The compressive strength of the solidified body is measured by a uniform load press and is 26.5 MPa. Compared with the compressive strength of the cement slurry solidified body without the addition of memory microspheres, which is 16.3 MPa, the compressive strength of the cement slurry solidified body with the addition of memory microspheres is increased by 63%, and the toughness is increased by 26%.
[0065] Example 5
[0066] The epoxy monomers used are E51 (21%) and 4.4-diaminodiphenylmethane tetraglycidylamine - TGMDA (3%), the curing agents used are triethylenetetramine TETA (8%) and 4,4' dithiodiphenylamine - DTDA (4%), the surfactants used are PVP30K (12%), SiO2NPs (0.8%), the volume ratio of ethanol to water is 5 / 5, the reaction is carried out in a constant temperature water bath at 85°C, the rotation speed is 300rpm, 100μl of accelerator DBU is added, and the reaction is carried out for 6h; the particle size D50 of the obtained microspheres is 1.7-2mm, the glass transition temperature Tg is 153°C, the compression rate is 40% at 173°C, and the shape recovery rate is 98% when the temperature is raised to 155°C.
[0067] The compressed memory microspheres (4%) were combined with calcium carbonate particles (8%) and fibers (0.2%), and added to 4% bentonite-based slurry to form an experimental slurry. A long crack (2×1mm) plugging experimental device was used to test the plugging performance of the plugging agent at 150°C, with a pressure of 9.2MPa and a leakage of 65ml. A comparative experiment was conducted using a plugging agent without memory microspheres, which resulted in complete leakage.
[0068] Example 6
[0069] The preparation method of the shaped polymer microspheres of this embodiment refers to the steps in Example 1, except that: the epoxy monomers used are E51 (20%) and 4.4-diaminodiphenylmethane tetraglycidylamine-TGMDA (4%), the curing agents used are 4,4-diaminodiphenyl sulfone-DDS (8%) and polyetheramine D230 (4%), the surfactants used are PVP30K (12%), SiO2NPs (1%), the volume ratio of ethanol to water is 5 / 5, the reaction is carried out in a constant temperature water bath at 85°C, the rotation speed is 300rpm, 100μl of accelerator DBU is added, and the reaction is carried out for 6h; the particle size D50 of the obtained microspheres is 2-2.2mm, the glass transition temperature Tg is 160°C, the compression rate is 35% at 180°C, and the shape recovery rate is 97% when the temperature is raised to 160°C.
[0070] The shape memory polymer microspheres of this embodiment are combined with pressed memory microspheres (5%), calcium carbonate particles (8%) and fibers (0.2%), and added to 4% bentonite-based slurry to form an experimental slurry. A long crack (3×2mm) plugging experimental device is used to test the plugging performance of the plugging agent at 160°C, with a pressure of 7.6MPa and a leakage of 115ml. In a comparative experiment, a plugging agent without memory microspheres is used, and all leakage occurs.
[0071] Example 7
[0072] The epoxy monomers used are E51 (17%) and trimethylolpropane triglycidyl ether -TMTGE (2%), and the epoxy monomers are dissolved in ethanol (50% of the total ethanol volume); the curing agents used are triethylenetetramine TETA (8%) and polyetheramine D230 (4%), and the curing agents are dissolved in ethanol (20% of the total ethanol volume); the surfactant used is PVP30K (12%), which is dissolved in ethanol (20% of the total ethanol volume), SiO2NPs (0.4%) are dispersed in ethanol (10% of the total ethanol volume), and the reaction is carried out in a constant temperature water bath at 85°C, the rotation speed is 300rpm, 100μl of accelerator DBU is added, and the reaction is carried out for 6h; the particle size D50 of the obtained microspheres is 900-930μm, the glass transition temperature Tg is 123°C, the compression rate is 43% at 148°C, and the shape recovery rate is 97% when the temperature is raised to 128°C.
[0073] The compressed memory microspheres (5%) were combined with xanthan gum (0.1%) and calcium carbonate particles (5%), and added to 4% bentonite-based slurry to form an experimental slurry. The plugging performance was tested at 123°C using a sand bed leakage test device. The sand bed penetration depth was 7.5cm and the pressure resistance was 10.3MPa. In a comparative experiment, no memory microspheres were added to the experimental slurry, the sand bed penetration depth was 14.8cm, and the pressure resistance was 6.1MPa, indicating that the addition of memory microspheres can effectively improve the plugging pressure resistance.
[0074] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing shape memory polymer microspheres, characterized in that: include: (1) mixing an epoxy resin, a curing agent, an organic solvent and a stabilizer to form a Pickering emulsion; (2) mixing the Pickering emulsion and the accelerator, reacting to obtain polymer microspheres, and pressing to obtain shape memory polymer microspheres; The stabilizer includes nanoparticles and / or nanosheets.
2. The method for preparing shape memory polymer microspheres according to claim 1, characterized in that: The stabilizer includes one or more of graphene nanosheets, zinc oxide nanoparticles, titanium dioxide nanoparticles, and silicon dioxide nanoparticles.
3. The method for preparing shape memory polymer microspheres according to claim 1 or 2, characterized in that: The mass content of the stabilizer in the Pickering emulsion is 0.08% to 1.6%.
4. The method for preparing shape memory polymer microspheres according to claim 1, characterized in that: The compression rate of the pressing is 20% to 50%; The pressing temperature is the glass transition temperature of the polymer microspheres + 20°C.
5. The method for preparing shape memory polymer microspheres according to claim 1, characterized in that: The stabilizer also includes a nonionic surfactant; The mass content of the nonionic surfactant in the Pickering emulsion is 5% to 12%.
6. The method for preparing shape memory polymer microspheres according to claim 1, characterized in that: The epoxy resin includes one or more epoxy monomers; The epoxy monomer contains 2 to 4 epoxy groups; The mass content of the epoxy resin in the Pickering emulsion is 9% to 24%; The curing agent includes a polyamine curing agent; The mass content of the curing agent in the Pickering emulsion is 5% to 12%; The accelerator includes a tertiary amine accelerator; The volume ratio of the Pickering emulsion to the accelerator is 1:(0.001-0.005).
7. The method for preparing shape memory polymer microspheres according to claim 1, characterized in that: The reaction temperature is 80-95° C. and the reaction time is 4-6 hours.
8. Shape memory polymer microspheres prepared by the method for preparing shape memory polymer microspheres according to any one of claims 1 to 7.
9. The shape memory polymer microsphere according to claim 8, characterized in that: The particle size is 5μm~2.2mm.
10. Use of the shape memory polymer microspheres prepared by the method for preparing shape memory polymer microspheres according to any one of claims 1 to 7, or the shape memory polymer microspheres according to claim 8 or 9, in the preparation of intelligent plugging materials for oil and gas drilling, cementing temperature-sensitive cement materials or cement expansion agent materials.
Citation Information
Cited By
Shape memory epoxy resin composite plugging material and preparation method thereof
CN121652545A